1986
DOI: 10.1136/bmj.293.6550.786
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of acute myocardial infarction with anisoylated plasminogen streptokinase activator complex.

Abstract: A controlled trial in 149 patients admitted to a district hospital with probable myocardial infarction tested the effect of 30 units of anisoylated plasminogen streptokinase activator complex (APSAC) on indices of infarct size. Patients were grouped prospectively according to whether they entered the trial within two and a half hours (early entry) or between two and a half and four hours (late entry) after onset ofthe symptoms. Sixty seven of 73 patients in the control group showed increased plasma activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(4 citation statements)
references
References 33 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…These trials were reported between 1983 and 1993 and indexed in the MEDLINE information system. 24 There are 22 such trials 12,13,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The indication for fibrinolytic therapy in two of the trials may not have been appropriate: the USIM trial included a high proportion (32%) of patients with unstable angina, and the ISIS-3 uncertain indication group consisted of patients without or with only minor ST elevation; 43,44 these patient subgroups are unlikely to benefit from fibrinolysis. [45][46][47] The USIM and ISIS-3 trials included 4250 patients who were treated within 3 h of symptom onset and may therefore seriously bias benefit estimations for early treatment of those with confirmed infarction.…”
Section: Methodsmentioning
confidence: 99%
“…These trials were reported between 1983 and 1993 and indexed in the MEDLINE information system. 24 There are 22 such trials 12,13,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The indication for fibrinolytic therapy in two of the trials may not have been appropriate: the USIM trial included a high proportion (32%) of patients with unstable angina, and the ISIS-3 uncertain indication group consisted of patients without or with only minor ST elevation; 43,44 these patient subgroups are unlikely to benefit from fibrinolysis. [45][46][47] The USIM and ISIS-3 trials included 4250 patients who were treated within 3 h of symptom onset and may therefore seriously bias benefit estimations for early treatment of those with confirmed infarction.…”
Section: Methodsmentioning
confidence: 99%
“…Significant ventricular arrhythmias occurred in 15 of 16 patients treated with anistreplase versus 13 of 18 controls in one They also occurred sooner after treatment: 142 versus 422 minutes.38 In another study, arrhythmias in the first 6 hours after treatment were more common with anistreplase than with placebo.30 Early ventricular tachycardia was significantly more frequent in anistreplase-treated patients than in controls (63% vs 37%; p < 0.05). 39 This was also confirmed using heparin-treated patients as a control group, again demonstrating a significant difference (48% vs 29%; p 0.002).= The earlier occurrence of arrhythmias with anistreplase may in fact signal earlier resolution of myocardial infarction.…”
Section: Arrhythmiasmentioning
confidence: 73%
“…The studies determined that anistreplase demonstrates a patency rate equivalent to that of intracoronary SK (51 % vs 60%). 16 In comparison to placebo or in open studies, anistreplase demonstrated earlier resolution of electrocardiographic (ECG) abnormalities, earlier peak enzyme release, and earlier occurrence of arrhythmia^.^^, 38,39 Two studies assessed the use of anistreplase before hospitalization; that is, patients were evaluated at home and received the drug from a mobile intervention team. Of 13 patients, 10 were considered treatment successes as assessed by noninvasive values of pain relief, and return to normal of ECG and reperfusion arrhythmia^.^^ Sixteen of 21 evaluable patients had clinical or ECG evidence of reperfusion within 2 hours of treatment.4' Patency was confirmed by angiography in 14 of the 16.…”
Section: Noninvasive Evaluationmentioning
confidence: 99%
“…When data are pooled 29 from studies for patients who had patent coronary arteries 90 minutes after dosing and who were inves tigated further by angiography 1 to 3 days later, reocclusion was found to have occurred in 4% in those patients receiving APSAC by comparison with 10% for SK. Other types of clinical trial have begun to ex amine the response to APSAC in a district hospital setting 36 and when administered before admission of patients to the hospital, in a mobile care unit. 37 For both types of trials the results are encouraging and provide support to the initiation of widespread use of APSAC.…”
Section: Clinical Trials In Acute Myocardial Infarctionmentioning
confidence: 99%